H46 The uncertainty of waiting: assessing the impact of the first Spanish meeting for premanifest and potential carriers of Huntington's disease. (12th September 2022) - Júlio, Filipa; Arnesen, Astri; Blanco, Ruth; Schepper, Beatrice De; Sousa, Dina De; Lis, Danuta; Olsen, Svein Olaf; Papantoniou, Giorgos; Ristolainen-Kotimäki, Saija; ,
Abstract : Background: The European Huntington Association (EHA) promoted the first event in Spain dedicated to premanifest and potential carriers of Huntington's Disease (HD). 52 individuals converged in Madrid for a national meeting entitled 'The Uncertainty of Waiting', which included a presentation about the EHA Moving Forward project, a debate about genetic testing moderated by a neuropsychologist, group dynamics and a get-together with snacks and drinks. Aims: This work aimed to assess the meeting impact through the participants' feedback. Methods: The EHA created an online survey to learn about the participants' impressions of the meeting. The participants' expectations towards HD organizations were also collected. The survey included open-ended and closed-ended questions and response percentages were analysed. Results: There were 34 survey respondents, 68% women, 44% under 35 years. Importantly, while 74% of respondents attended an HD meeting for the first time, 79% considered it very interesting and useful (particularly the debate) and 94% expressed interest in joining future HD-related events. HD research (79%) and coping strategies (76%) were signalled as preferred topics for upcoming meetings. Interestingly, most attendees reported their wish to get information (85%) and psychological support (79%) from HD associations. Conclusions: This meeting was a crucial entrance door for Spanish premanifest and potential HD carriers to connect with their peers and engage with local associations and healthcare professionals. The informal, non-clinical approach seems to be effective in getting these specific groups closer to information and support. Additionally, this event generated relevant topics to address in actions tailored to these groups.